Whole exome sequencing of microdissected splenic marginal zone lymphoma: a study to discover novel tumor-specific mutations. Issue 1 (December 2015) - Peveling-Oberhag, Jan; Wolters, Franziska; Döring, Claudia; Walter, Dirk; Sellmann, Ludger; Scholtysik, René; Lucioni, Marco; Schubach, Max; Paulli, Marco; Biskup, Saskia; Zeuzem, Stefan; Küppers, Ralf; et al.
Abstract Background Splenic marginal zone lymphoma (SMZL) is an indolent B-cell non-Hodgkin lymphoma and represents the most common primary malignancy of the spleen. Its precise molecular pathogenesis is still unknown and specific molecular markers for diagnosis or possible targets for causal therapies are lacking. Methods We performed whole exome sequencing (WES) and copy number analysis from laser-microdissected tumor cells of two primary SMZL discovery cases. Selected somatic single nucleotide variants (SNVs) were analyzed using pyrosequencing and Sanger sequencing in an independent validation cohort. Results Overall, 25 nonsynonymous somatic SNVs were identified, including known mutations in theNOTCH2 andMYD88 genes. Twenty-three of the mutations have not been associated with SMZL before. Many of these seem to be subclonal. Screening of 24 additional SMZL for mutations at the same positions found mutated in the WES approach revealed no recurrence of mutations forZNF608 andPDE10A, whereas theMYD88 L265P missense mutation was identified in 15 % of cases. An analysis of theNOTCH2 PEST domain and the whole coding region of the transcription factorSMYD1 in eight cases identified no additional case with aNOTCH2 mutation, but two additional cases withSMYD1 alterations. Conclusions In this first WES approach from microdissected SMZL tissue we confirmed known mutations and discovered new somatic variants. Recurrence ofMYD88 mutations in SMZL was validated, butNOTCH2 PEST domain mutations were relatively rare (10 % of cases). Recurrent mutations in the transcription factorSMYD1 have not been described in SMZL before and warrant further investigation.